Effect of intravenous l-carnitine in Chinese patients with chronic heart failure. (1st March 2016) - Jing, Zhi-Cheng; Wu, Bing-Xiang; Peng, Jian-Qiang; Li, Xin-Li; Pan, Lei; Zhao, Shui-Ping; Li, Dong-Ye; Yu, Zai-Xin; Gong, Jian-Bin; Zhao, Qing-Yan; Cao, Jia-Ning; Sheng, Guo-Tai; et al.
Abstract: Chronic heart failure (CHF) may be associated with an energy deficit in cardiac muscle. As levo-carnitine (LC) is involved in the production of myocardial energy, it is hypothesized that LC supplementation may ameliorate CHF symptoms. This multicentre, randomized, double-blind, and placebo-controlled study included 265 patients with CHF. Patients were randomized to receive either LC or placebo, twice a day. Endpoints were measured after 7 days of treatment. Primary endpoint was a reduction of at least one NYHA class. Secondary endpoints were changes in 6-min walk distance (6-MWD) compared with baseline, either alone or in combination with NYHA class decrease, left ventricular ejection fraction, and NT-proBNP level, together with adverse events. The primary endpoint was reached in 60.9% of patients treated with LC, compared with only 44.7% of the placebo group ( P = 0.012). Among the secondary endpoints, 6-MWD, alone or in combination with NYHA class, improved significantly in the LC group compared with placebo ( P = 0.0497 and P = 0.003, respectively). l -Carnitine was well tolerated. The lowest baseline values of plasma-free carnitine were observed in patients with NYHA classes III and IV where the effect of LC supplementation was greatest ( P = 0.002). Treatment with LC significantly improved CHF symptoms in Chinese patients, probably by correcting a status of carnitine insufficiency.